Mannoside recognition and degradation by bacteria. (20th December 2016) - Ladevèze, Simon; Laville, Elisabeth; Despres, Jordane; Mosoni, Pascale; Potocki‐Véronèse, Gabrielle
ABSTRACT: Mannosides constitute a vast group of glycans widely distributed in nature. Produced by almost all organisms, these carbohydrates are involved in numerous cellular processes, such as cell structuration, protein maturation and signalling, mediation of protein–protein interactions and cell recognition. The ubiquitous presence of mannosides in the environment means they are a reliable source of carbon and energy for bacteria, which have developed complex strategies to harvest them. This review focuses on the various mannosides that can be found in nature and details their structure. It underlines their involvement in cellular interactions and finally describes the latest discoveries regarding the catalytic machinery and metabolic pathways that bacteria have developed to metabolize them.